CENTRAL ASIA: NATO’S MILITARY-POLITICAL STRATEGY AND RUSSIA - SHAYMERGENOV, Timur (CENTRAL ASIA AND THE CAUCASUS, 2005)
Following the Soviet Union’s demise, the situation in Central Asia changed radically: it has become an object of attention of various regional and global geopolitical players. This region, which is rich in natural resources (primarily gold, oil, and gas) and which used to be off-limits for the leading geopolitical players with strategic interests in this key area, has now opened up and become an attractive playground for these various strategic forces.The United States, in its desire to consolidate its global leadership, is especially active there and is fully aware of the region’s strategic role as the heart of Eurasia. We can expect the United States to follow the geopolitical formula offered by prominent American political scientist Zbigniew Brzezinski, who declared “[he] who rules the World-Island [Eurasia] commands the world”1 and try, in the long-term perspective, to increase its influence in the region by every available means and method. It goes without saying that political influence in any corner of the globe rests on military presence. This is why the White House is out to strengthen the military component of its Central Asian policies by placing its military bases in some of the Central Asian states and Afghanistan. The events of 9/11 and the counterterrorist operation in Afghanistan, in which the U.S. was actively supported by its NATO allies, were used as a pretext to build up America’s influence in Central Asia. Indeed, while realizing its strategic conception, Washington is exerting strong ideo-logical influence on NATO, America’s main military ally.Today the Alliance’s strategic priorities have been transformed to fit the counterterrorist struggle and anticrisis measures being implement-ed during the military operation in Afghanistan (launched in October 2001) and the postwar settlement there. In fact, the U.S.-led counterterrorist operation made it possible for America and NATO to entrench themselves in Central Asia; their military presence there is also explained by the mounting tension worldwide.Today, Central Asia serves as the main strategic base for both Washington and NATO still engaged in post-conflict settlement in Afghanistan—this has tipped the regional balance of pow-er in favor of the U.S. and the EU and has some-what diminished the threat of proliferation of international terrorism. NATO is actively supporting its military presence in Central Asia by means of all-round political cooperation with the local states; in fact, we have already discerned the out-lines of NATO’s military-political strategy in Central Asia.